Shear strength of soil berm during lateral buckling of subsea pipelines. (September 2019) - Rismanchian, A.; White, D.J.; Randolph, M.F.; Martin, C.M.
Abstract: The soil resistance developed during temperature- and pressure-induced large lateral movements of shallowly embedded subsea flowlines is an important input parameter for the structural design process. A major source of uncertainty in calculation of the soil resistance is the undrained shear strength of the soil berm produced as the flowline moves across the seabed, which is affected by the level of remoulding. To investigate the effect of pipeline embedment and displacement amplitude on the shear strength of the berm, a set of centrifuge model tests was conducted on kaolin clay, involving laterally moving pipelines with constant embedments in the range 5%–35% of the pipe diameter. Back-analysis of the test results, using finite element limit analysis, showed that the shear strength of the soil berm is a function of pipe displacement amplitude, pipe embedment, and soil sensitivity. On the basis of these results, we propose that the overall berm undrained shear strength may be determined as a convolution of the shear strengths of its constituent soil elements. Finally, a formula is presented for calculating the shear strength of soil elements within the soil berm, and this is used to back-analyse the overall soil berm resistance from the model tests.